Methodology of ECG Interpretation in the Hannover Program - Zywietz, Chr.; Borovsky, D.; Gotsch, G.; Joseph, G. (Methods of Information in Medicine, 1990)
The Hannover ECG program HES has been designed for measurement and interpretation of resting and (moderate) exercise electrocardiograms. In the signal analysis part the program follows an averaging strategy. For diagnostic classification a hybrid model with decision trees and scoring algorithms, and with multivariate probabilistic tests for derivation of category A statements is applied. The multivariate classification technique allows to adjust sensitivity and specificity for specific application areas without changing the diagnostic criteria.
Keywords: Decision support; Computer ECG analysis; Evaluation